The Integrated Business Model's Contributory Role Towards Financial Performance: Women Directors’ One Third Presence - Baharudin, Dayana Mastura; Marimuthu, Maran; Shahimi, Suhaily (Business Management and Strategy, 2021)
The goal of this study is to see how consolidated business model exposures in the Integrated Report or Annual Report affect the top 30 Malaysian PLCs, moderated by the MCCG 2017 recommendation of including 30% of women on the board of directors. In order to analyze the Integrated Business Model exposures among the top 30 Malaysian PLCs, the study uses a purposeful sampling technique coupled with predictive analysis, multiple regression analysis, and quantitative analysis derived from previous studies, as well as a summary of annual reports and integrated reports. The construction of a new Female Governing Board Content-Scoring Index will identify the best policies of the top 30 Malaysian PLCs, which will benefit both researchers and business players outside of the top 30. This research is a systematic study of detailed methodological developments in Integrated Business Model disclosures reported through the Integrated Report and Annual Reports of the top 30 Malaysian PLCs, in terms of uniqueness. In conclusion, with regards to the acceptance of the Integrated Business Model , the results show significance in terms of Return on Assets which reflects internal top management’s acceptance, which is also in congruence with the significance shown in terms of Return on Equity which reflects external investors and shareholders’ acceptance, and finally are also symmetrical to the significance results shown in terms of TobinsQ which reflects the market participants.